NILAI TBA, FFA, KADAR AIR DAN SIFAT SENSORI KERIPIK KENTANG BERDASARKAN JENIS KEMASAN DAN LAMA PENYIMPANAN - Azqia Fajriyani; Wikanastri Hersoelistyorini; nurhidajah nurhidajah (Universitas Muhammadiyah Semarang, 2019)
Potato (Solanum tuberosum L.) is one type of tubers are widely consumed by the community because it tastes good and contains high carbohydrates. Potato damage easily occurs because the water content in potatoes is high enough that is 80 percent. Based on that, it is necessary to do the processing to extend the life of the potato store. This study aims to determine the effect of packaging type and storage time to the value of TBA, FFA, Water Content and Sensory Character of Potato Chips. This study used a factorial completely randomized design consisting of 2 factors: packaging type (PP, PE, and aluminum foil) with each thickness of 0.5 mm and storage time (0 days, 7 days, 14 days, 21 days and 28 day) in room temperature. The result of statistical test showed that the type of packaging and storage time had an effect on FFA value, water content and sensory character of potato chips while the value of TBA had no significant effect. Level of potato chip TBA at end of shelf in packing PP 2,412 mg malonaldehid / kg sample, PE 3,365 mg malonaldehid / kg and aluminum foil 2,787 mg malonaldehid / kg sample. FFA value at end of shelf life on packing PP1,173% ALB sample, PE 1,548% ALB sample, and Alumunium foil 1.173% ALB sample. Water content at end of shelf life on PP 7.040%, PE 3,933%, and Alumunium foil 3,003%. The result of statistical test shows that there is influence of packaging type and storage time to FFA value, water content and sensory character of potato chips.